Spatiotemporal analysis of glacial retreat at the Coropuna and Solimana volcanoes in Peru, using NDWI calculation between 1986 - 2022 - Viera Castañeda, Fabrizio Alexander (2023)
21st LACCEI International Multi-Conference for Engineering, Education, and Technology: “Leadership in Education and Innovation in Engineering in the Framework of Global Transformations: Integration and Alliances for Integral Development”, Hybrid Event, Buenos Aires - ARGENTINA, July 17 - 21, 2023.